FROM METAPHYSICAL TO POLITICAL: DOES POLITICAL CULTURE MAKE RAWLS’S PRINCIPLE OF TOLERANCE MORALLY RELATIVISTIC? - Vranic, Bojan M (Politeia, 2017)
The aim of this paper is to analyze Rawls’s conception of political (public) culture, exploring whether his principle of tolerance (Political Liberalism) falls in the moral relativism. The analysis consists of three sections. Firstly, the author introduces different critical accounts on Rawls’s theory and identify where do they go wrong. Secondly, the author delineates the intellectual tradition of social liberalism from which sprang Rawls’s conception, showing that he significantly alters the key ideas of dominant liberal justice of the Western world. In the final section of the paper it is argued that Rawls’s idea of political culture is a cornerstone of just society and the spring of tolerance, providing arguments in favor of the idea that Rawls’s conception of political liberalism is not morally relativistic but it is in line with liberal pluralism.
Keywords: moral relativism; political culture; Rawls; political liberalism; metaphysics; concepts